Efeito da calagem na produtividade e qualidades agroindustriais da cana-de-açúcar (Saccharum officinarum L.), em latossolo vermelho amarelo. - (:unkn) unknown (Universidade Federal do Amazonas, 2011)
The expansion of cultivation of sugarcane in areas of soil with acid characteristics and low fertility limit the potential for productivity and quality of sugarcane. In the present study aimed to evaluate of varieties of sugarcane at levels of lime under field conditions in the city of Presidente Figueiredo, in Amazonas State. The experimental design was a randomized block design with three replications in a factorial scheme 7x4, with seven levels of lime (0.0; 1.0; 2.0; 3.0; 4.0; 5.0 and 6.0 t ha-1) and four varieties of sugarcane (CO - 997, RB - 72454, RB - 835019 and RB 835486) at the stage of plant cane. After 14 months of conducting the experiment were made the cut stem to analyze the characteristics: stem production; Brix, pol and juice purity, and pol, fiber, reducing sugar (AR) and total recoverable sugar (ATR) of cane. There was no interaction effect between levels and varieties in any of the variables, and not isolated effects of factor limestone. Moreover, the response of varieties to lime rates was significant, except for characteristic juice purity. In general the setting, did not interfere significantly in productivity, despite the increase in gains of up to 50.5% of the level over six zero level. Thus, as there was no effect on the qualities of agroindustrial sugarcane. Being only observed for varieties of sugarcane, compared to average levels. The behavior of those characteristics were very dependent on the varieties studied, so that the variety RB 835486, responded better in yield and fiber characteristics. Since the characteristics of the juice brix and pol, pol and ATR cane, variety RB 835,019, was one that proved superior to others, and in the variety AR was higher CO 997.
Keywords: Correção do solo; Cana planta; Cana-de-açúcar; Presidente Figueiredo - Amazonas; CIÊNCIAS AGRÁRIAS: AGRONOMIA